Implementation Agreement of Confucius Institute Exchange between Hebei University and UMP - Yong, Ying Mei (2019)
Hebei, 6 & 7 December 2018- Exchange Ceremony of Implementation Agreement between Hebei University and Universiti Malaysia Pahang (UMP) for the development of Confucius Institute (CI) at UMP has been organized at Hebei University (HBU), China.